(untitled) (InKoj. Philosophy & Artificial Languages, New series, 2010)
el: Violin Oljanov (red.). Interlingvistiko Esperantologio. Sofio: Bulgara Esperantista Asocio. 1985. pp. 19–43. Antaŭparolo de Federico Gobbo